Oral manifestations in subjects with sexually transmitted diseases - An, Margareth Y Obara; Câmara, Jeconias; Oliveira, Lucileide C.; Silva, Maria do Rosario A.; Benzaken, Adele S. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Introduction: despite the technological progresses that have taken place in the medical field in the last decades, STD persist to be an aggravating factor in public health. This is perhaps due to the lack of knowledge of our transmission mechanisms. Particularly, the role of the oral cavity in the transmission and development of STD has not been the subject of many detailed studies. This study aims to reduce the information vacuum in our municipality, as well as contribute to the knowledge of epidemiology in STD in our field. Objective: investigating the prevalence of oral manifestations of sexually transmitted diseases (STD) in infected individuals in Manaus, Amazon, in the year 2008. Methods: 157 people with confirmed clinical and laboratorial STD diagnosis undergoing treatment at the Alfredo da Matta Foundation. The oral lesions were detected by oral clinical examination and microscopic techniques for cells and tissue studies. Results: in 24,2% participants 46 (29,1%) oral lesions were observed, which could possibly linked to STDs. Direct correlation was observed between educational level and knowledge of oral lesions and STD, but no correlation was found between oral lesions and oral sexual practice, educational level or oral hygiene. The statistical analysis was done on SPSS (95% confidence level) and chi-square tests were applied. Conclusion: this study showed the existence of a hidden population of individuals with needs on precocious oral lesions diagnosis, treatment and referring for other specialized services, for example, the Oncology, considering the risk of malignancy of some lesions. The necessity to establish a stomatology service in the Amazon must be considered.